Medical students’ perception of the use of artificial intelligence in medical education - Wobo, Kininyiruchi Nelson; Nnamani, Ifeoma Ogonna; Alinnor, Ezioma Anne; Gabriel-Job, Nneka; Paul, Nsirimobu (International Journal of Research in Medical Sciences, 2024)
Background: Artificial Intelligence (AI) refers to technology that can efficiently perform tasks that typically require human intelligence, such as decision-making, teaching, object detection, and solving complex problems. As a veritable tool in medical education, this study was conducted to assess medical students’ awareness, perception and usage of AI in learning. Methodology: This study was conducted at the Department of Paediatrics, University of Port Harcourt Teaching Hospital (UPTH). The subjects were one hundred and thirty-nine 5th-year medical students who had completed 3 months of Paediatrics and Obstetrics/Gynaecology clinical rotations. Data was collected using a semi-structured, open-ended questionnaire. Data were analysed using IBM SPSS Statistics version 26. Statistical significance was set at p value<0.05. Results: 64 (46%) of the respondents are aware of AI. 57 (44%) of respondents applied AI during their clinical training. The most commonly used AI tool is Chatbots. 57(100%). The major limitations to AI use were unreliable internet connectivity (62%) and the high cost of AI hardware and software (53%). Most respondents (68%) expressed ethical concerns about the use of AI. There was a statistically significant relationship between awareness of AI and the use of AI in learning (p=0.0001) Conclusion: This study demonstrates average awareness of AI’s use and benefits among medical students. The major limitations to using AI were unlimited internet connectivity and the cost of AI tools. To maximize the benefits of AI in medical education in developing countries, medical schools need to increase their awareness and infrastructural capacity.